2016
DOI: 10.3846/20294913.2015.1125965
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Economic Growth: A Review

Abstract: The objective of this paper is to review and attempt a synthesis of the relevant literature on growth versus poverty, and to analyze the causal link between the two phenomena. Research issues that drive our study are: Does economic growth tend to “raise all boats” as Kuznets (1955) pointed out? What is the role of the pattern of growth in the process of development? Which factor must we consider in designing appropriate pro-poor growth policies? This paper finds considerable variation in the poverty–reducing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 44 publications
1
30
0
3
Order By: Relevance
“…This fact can generate a high level of inequality and poverty, and insufficient productive opportunities for employment [31]. Taking into account that economic growth by itself may not be inclusive and sustainable [32], the nature and pattern of economic growth matters for employment creation and poverty reduction.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact can generate a high level of inequality and poverty, and insufficient productive opportunities for employment [31]. Taking into account that economic growth by itself may not be inclusive and sustainable [32], the nature and pattern of economic growth matters for employment creation and poverty reduction.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…The research results showed that economic growth in some EU countries (countries in clusters 2 and 3) should be more sustained and inclusive, and sufficiently employment intensive, such that more job opportunities for a larger workforce are created, and workers, especially those who are poor, benefit from improvements in standards of living [16]. Thus, an important challenge for policy-makers is to mix pro-growth and pro-poor policies [32]. As WEF report [60] (p. 6) states, "a new growth model that places people and living standards at the center of national economic policy and international economic integration is required to transform inclusive growth from aspiration into action in the Fourth Industrial Revolution".…”
Section: Conclusion and Main Implicationsmentioning
confidence: 99%
“…Dalam kaitannya dengan pertumbuhan ekonomi, secara literatur, kemiskinan merupakan salah satu faktor yang dapat mempengaruhi pertumbuhan ekonomi. Para ekonom setuju bahwa kemiskinan dan pertumbuhan ekonomi memiliki hubungan terbalik atau negatif (Alvaredo & Gasparini, 2015;Garza-Rodriguez, 2018;Karim et al, 2013;Škare & Družeta, 2016). Studi lain juga menyatakan bahwa perlambatan pertumbuhan ekonomi telah menyebabkan adanya kemiskinan (Aba et al, 2015).…”
Section: Kajian Pustaka Dan Perumusan Hipotesisunclassified
“…Merujuk pada tabel 4 yang terdapat di lampiran, tampak kemiskinan berkurang dan hal ini menunjang pertumbuhan ekonomi di wilayah induk. Hal ini sejalan dengan studi Alvaredo & Gasparini (2015); Garza-Rodriguez (2018); Karim et al (2013); Škare & Družeta (2016) bahwa kemiskinan dan pertumbuhan ekonomi memiliki hubungan terbalik atau negatif.…”
Section: Pada Wilayah Indukunclassified
“…One of the important factors to increase the economic activities and growth is Human Resources (HR) quality. This might happen because the main resource of an economic growth is basically humans themselves (Skare & Blazevic, 2015). The allocation of the qualified human resources is a necessary condition for an economic growth.…”
Section: Introductionmentioning
confidence: 99%